2007
DOI: 10.1016/j.jep.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sutherlandia frutescens extracts on cell numbers, morphology and gene expression in MCF-7 cells

Abstract: Sutherlandia frutescens is a well-known South African herbal remedy traditionally used for stomach problems, internal cancers, diabetes, various inflammatory conditions and recently to improve the overall health in cancer and HIV/AIDS patients. The influence of crude Sutherlandia frutescens extracts (prepared with 70% ethanol) was investigated on cell numbers, morphology, and gene expression profiles in a MCF-7 human breast adenocarcinoma cell line. Time-dependent (24, 34, 48 and 72 h) and dose-dependent (0.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Based on the morphological features observed, including cell shrinkage, spherical cell shape and plasma membrane blebbing, the treated cells can be classified as apoptotic (Kroemer et al, 2009). These findings are consistent with previous studies which have also found morphological characteristics of apoptosis following S. frutescens treatments of various cell lines (Chinkwo, 2005 andStander et al, 2007).…”
Section: Effect Of Extracts On Pbmcssupporting
confidence: 93%
See 3 more Smart Citations
“…Based on the morphological features observed, including cell shrinkage, spherical cell shape and plasma membrane blebbing, the treated cells can be classified as apoptotic (Kroemer et al, 2009). These findings are consistent with previous studies which have also found morphological characteristics of apoptosis following S. frutescens treatments of various cell lines (Chinkwo, 2005 andStander et al, 2007).…”
Section: Effect Of Extracts On Pbmcssupporting
confidence: 93%
“…Under these conditions almost all the extracts are able to produce a significant decrease in cell viability. These concentrations are similar to the concentrations of S. frutescens used in previous studies (Tai et al, 2004;Chinkwo, 2005;Stander et al, 2007;Stander et al, 2009;Korb et al, 2010 andPhulkkdarre, et al 2010). The ATP assay supported that the extracts do in fact significantly decrease the cell viability as detected by alamarBlue® at concentrations of 2.5 and 5 mg/ml ( Fig.…”
Section: Effect Of Extracts On Pbmcssupporting
confidence: 88%
See 2 more Smart Citations
“…It has been investigated for many of the anecdotal claims. Many of such studies have suggested its potential for beneficial effects in HIV/AIDS (Harnett et al, 2005), cancer (Stander et al, 2007(Stander et al, , 2009Skerman et al, 2011), diabetes (Chadwick et al, 2007;Mackenzie et al, 2009Mackenzie et al, , 2012, inflammation (Ojewole, 2004), microbial infection (Katerere and Eloff, 2005), stress (Prevoo et al, 2004), and convulsion (Ojewole, 2008). Commercial twice-daily Sutherlandia capsules containing 300 mg of powdered dried leaves are also available in the herbal medicines shops in South Africa (Van Wyk and Albrecht, 2008).…”
Section: Introductionmentioning
confidence: 99%